From Discrimination Towards The Justice Of Law (A Study Of Marriage Registration For Adherent Of Belief) - asian journal of law; humanity; Syarifa Khasna (Faculty of Sharia, State Islamic University KH. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2021)
The existence of adherents of belief in Indonesia is still discriminated against regarding their legal standing in the front of the State, especially regarding the issue of marriage registration. Adherents of belief are not included in the religion recognized by the state so that it is difficult to register their marriages. This is important to discuss because marriage registration will affect the marital legal standing and is related to the state'sobligation to provide justice and equal rights. This article discusses the legal justice of marriage registration for adherents of belief using the normative juridical method. The results of the study indicate that although the state has regulated the procedure for registering marriages for adherents of belief, there are still many adherents of belief who experience problems in registering marriages because not all religious organizations are registered. This is phenomenon are deemed not in line with the implementation of the 1945 Constitution which guarantees the constitutional rights of adherents of belief, including the registration of marriages.